Perilipin-2 is associated with a higher risk of microvascular obstruction in ST-elevation myocardial infarction patients undergoing primary percutaneous coronary intervention. (25th November 2020) - Russo, M; Montone, R.A; D'Amario, D; Camilli, M; Canonico, F; Santamaria, C; Iannaccone, G; Meucci, M.C; Gurgoglione, F; Severino, A; Liuzzo, G; Niccoli, G; et al.
Abstract: Background: Coronary microvascular obstruction (MVO) is a noxious condition frequently occurring in patients with ST-elevation myocardial infarction (STEMI) after percutaneous coronary intervention (PCI). However, multiple mechanisms are involved in the pathogenesis of MVO and not yet fully understood. Recent studies suggested that perilipin 2 (PLIN2) may play an important role in lipid metabolism of macrophages resident in atherosclerotic plaques along with a role in enhancing oxidative stress. Purpose: To study the association between PLIN2 and MVO in STEMI patients undergoing primary PCI. We also assessed the role of PLIN2 to predict future major cardiovascular events (MACEs). Methods: STEMI patients undergoing primary PCI were enrolled. PLIN2 was dosed within 24 hours from admission in peripheral blood monocytes. MVO was assessed using TIMI flow grade and myocardial blush grade on coronary angiogram after PCI, and patients were stratified accordingly (MVO or noMVO). Major adverse cardiac events (defined as a composite of cardiac death, non-fatal myocardial infarction, re-admission for heart failure and target vessel revascularization) were assessed at clinical follow-up. Results: Among 100 STEMI patients (mean age, 65.2±12.0 years, 81 males), 33 (33.0%) had MVO. Patients with MVO were older, had higher troponin I peak, C-reactive protein and lower left ventricular ejection fraction on admission. Patients with MVO had significantly higher levels of PLIN2 (1.03±0.28 vs. 0.90±0.16, p=0.019) compared to noMVO patients. Age [OR (95% CI) per year, 1.045 (1.005–1.087), p=0.026] and PLIN2 [OR (95% CI) per unit, 16.606 (2.027–136.030), p=0.009] were associated with MVO at univariate logistic regression analysis. However, only PLIN2 levels [OR (95% CI) per unit, 12.325 (1.446–105.039), p=0.033] were independently associated with MVO at multivariate analysis. Follow up data were available for 76 patients (76%). After a mean follow up of 182.2±126.6 days, 13 MACEs occurred. Patients with MVO had more MACEs [9 (37.5%) vs. 4 (7.7%), p<0.001] compared to noMVO patients. At univariate Cox regression analysis, MVO [HR (95% CI), 6.792 (2.053–22.460), p=0.002], hypercholesterolemia [HR (95% CI), 3.563 (1.094–11.599), p=0.035] and PLIN2 [HR (95% CI) per unit, 82.991 (9.857–698.746), p<0.001] were predictors for MACEs at follow up. At multivariate analysis only PLIN2 [HR (95% CI) per unit, 26.904 (2.461–294.100), p=0.007] was an independent predictor of MACEs. Conclusions: In STEMI patients undergoing primary PCI, PLIN2 was independently associated with MVO. PLIN2 was an independent predictor of MACEs at clinical follow-up. These findings suggest that PLIN2 may represent a promising therapeutic target, opening the avenue towards novel therapeutic approaches for MVO. Funding Acknowledgement: Type of funding source: None